LITERASI DIGITAAL PENGGUNA SOSIAL MEDIA LEMBAGA SENSOR FILM INDONESIA - Ismail, Ervan; Atmodjo, Juwono Tri; Rahman HI, A. (Universitas Mercu Buana, 2023)
The development of the use of information technology by the public, the development of website-based information technology used by the |Film Censorship Institute and the demands of stakeholders from government institutions, the Film Censorship Institute, to adapt their duties, roles, functions and ways of communicating with the public on the one hand, and on the other hand forTo get an overview of users' digital literacy with the title Digital Literacy of Social Media Users, Indonesian Film Censorship Institute using a qualitative approach with a case study research strategy. The sata collection technique was carried out using in-depth interviews and documentation studies. The informants in this research are social media users, stakeholders of the Film Censorship Institute.Based on research findings, the elements of digital literacy include: creativity, critical thinking skills and the ability to disseminate digital message content, social and cultural understanding, the ability to collaborate with other people, the ability to obtain and select information, effective communication, digital security, and functional skills that obtained from the use of social media Instagram and Tik Tok from the Film Censorship Institute.There are three levels or categories of literacy, namely: (a). literacy obtained directly from sources or messages produced by LSF for knowledge and self-protection (e_safety); (B). Information literacy from messages communicated between LSF Instagram followers; and (c). Literacy related to the use of messages or information to communicate and collaborate with other people via social media or interpersonal communication.Digital literacy obtained is in the form of knowledge and experience, people's creativity, critical thinking, people's culture or way of life, socialization with other people online, and as a vehicle for searching for information about film entertainment among other online entertainment, self-protection (e_safety) and functional abilities.